47.1k views
5 votes
Jay solved the following equation for x what did she do wrong

Jay solved the following equation for x what did she do wrong-example-1

1 Answer

4 votes

SOLUTION

Write out the equation


4(x+6)-11=25

To fid the value of x, we do the following

Expand the paranthesis


4x+24-11=25

11 is outside the paranthesis, hence we don't multiply it by 4

The simplify the expression


4x+13=25

Subtract 13 from both sides, we have


\begin{gathered} 4x+13-13=25-13 \\ 4x=12 \end{gathered}

Divide both sides by 4, we have


\begin{gathered} (4x)/(4)=(12)/(4) \\ \text{Then} \\ x=3 \end{gathered}

Therefore

x=3

Hence

Jay was wrong when she multiply -11 outside the paranthesis by 4

User Gianfranco P
by
4.7k points